Oxidation resistance and microstructure of Pt and PtIr diffusion coatings on Ni based single crystal superalloys by electroplating method - Tue, Dao Chi; Murakami, Hideyuki; Hong Lien, Le Thi (Vietnam Journal of Science and Technology, 2019)
In this study, Pt and PtIr diffusion coatings on Ni based single crystal superalloys were fabricated by an electroplating method followed by an annealing heat treatment process. The microstructure and phase constitution of the coatings were studied by SEM/EDS and XRD methods. The cyclic oxidation test at 1150oC was conducted to investigate the oxidation resistance of the coatings. The results showed that the addition of Ir in the coating led to the formation of α(NiPt2Al) phase and reduced the formation Kirkendall voids in the coating after 100 cycle oxidation test